SAT0053 Persistence of Subclinical Joint Activity in Rheumatoid Arthritis Joints. (10th June 2014) - Gärtner, M.; Alasthi, F.; Supp, G.; Mandl, P.; Smolen, J.; Aletaha, D.
Abstract : Background: Ultrasound (US) assessment was shown to be a sensitive tool for the evaluation of joint activity in patients with rheumatoid arthritis (RA). Synovial effusion and synovial hypertrophy can be evaluated by gray scale (GS), while hypervascularisation, as a marker of inflammation, can be measured using power Doppler signals (PD). Both types of signals are highly sensitive, and may persist even in clinical inactivity, i.e. when swelling or tenderness are absent. It is conceivable that such subclinical US signals may resolve if clinical inactivity is sustained, but this has not yet been shown during long-term follow-up. Objectives: To investigate the persistence of subclinical US signals in previously clinically active joints in relation to prolonged clinical inactivity. Methods: We performed US imaging including GS and PD, each graded on a four point scale (0=no, 1=mild, 2=moderate and 3=marked) of 22 joints of the hands of RA patients. We then selected all joints with no clinical activity at the time of the US examination. Based on a routine clinic database with 3-monthly joint assessments, the last time point of clinical joint activity (swelling, tenderness or both) was identified. The time between the last clinical joint activity and the current sonographic assessment in that joint was determined and persistence of subclinical US activity was estimated for all patients and all joints. Results: We assessed a total of 1980 joints in 90 RA patients. 1329 (67.1%) joints were positive on GS and 410 (20.7%) showed PD signals. The median (IQR) time between the last visit exhibiting swollen or tender joint(s) and the US assessment showing PD/GS-signals in the same now clinically inactive joint(s) was 3.6 (1.2; 6.3) and 3.5 (1.3; 5.6) years, respectively. We found that the time between last clinical activity (swelling and/or tenderness) and positive sonographic assessment was significantly shorter in joints showing GS signals ≥2 than in joints with GS=1 (median [IQR] 2.6 [0.6; 2.6] vs. 3.9 [1.9; 6.6]; p<0.001), for PD signals there was also a trend towards shorter periods of clinical remission in highly active joints (median [IQR] of 2.4 [0.5; 5.3] for PD≥2 vs. 4.3 [1.0; 6.2] for PD=1; p=0.066). In joints showing highly positive GS and PD signals (both ≥2), the time to the last clinical activity was even shorter, with a median of 1.4 years. (Figure 1 ) Conclusions: We conclude that subclinical joint activity is long lasting in RA joints in clinical remission, but resolves over time. The latter is indicated by a shorter period from last clinical activity for strong signals (PD ≥2, GS ≥2) as compared to weak signals (PD ≤1, GS ≤1). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3247